1996
DOI: 10.1128/aac.40.12.2743
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of dapsone administered biweekly to human immunodeficiency virus-infected patients

Abstract: The population pharmacokinetics of dapsone were examined in human immunodeficiency virus-infected patients receiving dapsone at a dosage of 100 mg twice weekly for the prevention of Pneumocystis carinii pneumonia. Nonlinear mixed-effect modeling was used to determine the best pharmacostatistical model for the data. A one-compartment open model with first-order absorption and elimination was used as the structural pharmacokinetic model. Several covariates were tested for their influence on pharmacokinetic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
5
14
0
Order By: Relevance
“…These data raise the question of whether dapsone could be effectively used in PCP prophylaxis in pediatrics at a lower dose, where methemoglobinemia risk was much lower. Pharmacokinetic data from HIV patients suggest that this is indeed possible, with efficacy and adequate lung penetration evident when given once per week1718. Several subsequent studies in pediatric HIV have suggested that 2–3 times weekly dosing of 2mg/kg results in acceptable drug levels and lung penetration1921.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data raise the question of whether dapsone could be effectively used in PCP prophylaxis in pediatrics at a lower dose, where methemoglobinemia risk was much lower. Pharmacokinetic data from HIV patients suggest that this is indeed possible, with efficacy and adequate lung penetration evident when given once per week1718. Several subsequent studies in pediatric HIV have suggested that 2–3 times weekly dosing of 2mg/kg results in acceptable drug levels and lung penetration1921.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic data from HIV patients suggest that this is indeed possible, with efficacy and adequate lung penetration evident when dapsone was given once per week. 17,18 Several subsequent studies in pediatric HIV have suggested that 2 to 3Â times weekly dosing of 2 mg/kg results in acceptable drug levels and lung penetration. [19][20][21] One study comparing dapsone dosing (1 mg/kg/d vs 4 mg/kg/wk vs 2 mg/kg/d) in 94 pediatric HIV-positive children demonstrated no statistically significant difference in PCP breakthrough.…”
Section: Discussionmentioning
confidence: 99%
“…Dapsone has been suggested as a CYP3A model drug, [111][112][113][114][115] and dapsone metabolism is affected by CYP3A inducers and inhibitors. 116 Thus, the induction of CYP3A by UDCA might enhance the biotransformation of dapsone, resulting in a reduced efficacy. The tissue distribution of drugs is determined by their transport across membranes.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…Dermatitis herpetiformis improved markedly after discontinuation of UDCA treatment, and exacerbated again following the reintroduction of UDCA. Dapsone has been suggested as a CYP3A model drug, 111–115 and dapsone metabolism is affected by CYP3A inducers and inhibitors 116 . Thus, the induction of CYP3A by UDCA might enhance the biotransformation of dapsone, resulting in a reduced efficacy.…”
mentioning
confidence: 99%
“…It has been suggested that rifampin decreases the serum concentration of dapsone through the induction of CYP3A4 and, indeed, one study has shown dapsone clearance to be increased by between 69% and 122% [42]. It was not clear whether this reduction in concentration would result in a decreased efficacy in clinical practice [43], though some experts believed this to be the case [44].…”
Section: Rifampinmentioning
confidence: 96%